IS THERE THE RADICAL RIGHT IN LITHUANIA? - Zaremba, Aurimas (Politologija, 2013)
The main goal of the article is to analyze the situation of radical right in Lithuania and to answer the question whether there is the radical right in Lithuania. The article begins with a review of the problems of the definition of radical right; also the radical right ideology and programmed provisions are described. The situation of radical right in Lithuania is analysed through an interview study of experts of Lithuanian politics. Two most commonly used definitions of right-wing radicals are radical right and extreme right. However, extreme right is related to anti-democratic and anti-system features which are alien to liberal democracy. Therefore, the ‘term radical’ right should be used, and radical right should be understood as a family of political parties which use ideology based on nationalism, the idea of a strong state and the use of exclusion criteria as well as the radical, uncompromised way of action. Nationalism is related to ethnocentrism, anti-communism, euroscepticism, the ideas of internal homogeneity, and external isolation. The idea of strong state is revealed through militarism, society based on law and order, authoritarianism, the idea of one leader, and antipluralism. The use of exclusion criteria includes the growing opposition to immigration, xenophobia, and hostility to ethnic or sexual minorities. The most representative provisions of a radical right party’s political programs are a strong opposition to immigration, the negative attitude towards ethnic and sexual minorities, globalization, multiculturism and euroscepticism, the emphasis on ethnicity and the traditional way of life, the desire to strengthen crime control and to increase penalties for violations of law. There are no clearly expressed radical right parties in Lithuania. On the other hand, there are other parties that use the radical right ideas, symbols or rhetoric. Such are the Order and Justice Party, the Nationalist Union, the Lithuanian Center Party, and the party “Young Lithuania”. The Lithuanian politicians Petras Grazulis, Gintaras Songaila, Kazimieras Uoka, and Stanislovas Buskevicius can be called radical right politicians. However, neither they nor other politicians of Lithuania can be described as charismatic leaders who can lead the radical right. It is difficult to identify the prospects of radical right in Lithuania; they will depend on the further development of the country’s social, economic, demographic, cultural, and political situation.